2021
DOI: 10.1136/jitc-2020-001819
|View full text |Cite
|
Sign up to set email alerts
|

Integrating genome-wide CRISPR immune screen with multi-omic clinical data reveals distinct classes of tumor intrinsic immune regulators

Abstract: BackgroundDespite approval of immunotherapy for a wide range of cancers, the majority of patients fail to respond to immunotherapy or relapse following initial response. These failures may be attributed to immunosuppressive mechanisms co-opted by tumor cells. However, it is challenging to use conventional methods to systematically evaluate the potential of tumor intrinsic factors to act as immune regulators in patients with cancer.MethodsTo identify immunosuppressive mechanisms in non-responders to cancer immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…The study identified receptorinteracting serine/threonineprotein kinase 1 (RIPK1) as a potential druggable target that upon inhi bition sensitizes tumours to antitumour T cell cytotoxic ity. Consistent with the genetic screen, pharmacological RIPK1 inhibition sensitized tumours to immunotherapy in a preclinical transplant model 242 . As a result of this study, a RIPK1 inhibitor proceeded into clinical trials, although ultimately did not achieve its predefined end point 243 .…”
Section: Identifying Gene Interactionsmentioning
confidence: 76%
See 1 more Smart Citation
“…The study identified receptorinteracting serine/threonineprotein kinase 1 (RIPK1) as a potential druggable target that upon inhi bition sensitizes tumours to antitumour T cell cytotoxic ity. Consistent with the genetic screen, pharmacological RIPK1 inhibition sensitized tumours to immunotherapy in a preclinical transplant model 242 . As a result of this study, a RIPK1 inhibitor proceeded into clinical trials, although ultimately did not achieve its predefined end point 243 .…”
Section: Identifying Gene Interactionsmentioning
confidence: 76%
“…CRISPR screens using immune cell-tumour cell cocultures and in vivo transplants in immunecompetent hosts have been used to iden tify tumourintrinsic factors that govern tumourimmune interactions (reviewed in 241 ). In one example, a genomewide screen using cancer cells cocultured with cytotoxic T cells revealed cancer cellintrinsic regulators of T cell killing 242 . The study identified receptorinteracting serine/threonineprotein kinase 1 (RIPK1) as a potential druggable target that upon inhi bition sensitizes tumours to antitumour T cell cytotoxic ity.…”
Section: Identifying Gene Interactionsmentioning
confidence: 99%
“…Deletion of PRMT1 using CRISPR-Cas9 sensitizes the colon adenocarcinoma cell line, MC38, to anti-programmed cell death protein-1 (PD-1) immunotherapy. 107 Inhibiting PRMT1 was shown to sensitize tumors to T cell-mediated killing by enhancing the apoptosis of cancer cells. Furthermore, transcriptomic analysis showed that PRMT1 knockout alters the expression of genes involved in T cell-mediated tumor apoptosis and in the production of cytokines and chemokines such as CCL7 and CCL9.…”
Section: Prmts In Cancer Immunotherapymentioning
confidence: 99%
“…MLLT6 loss mitigates the inhibition of CD8 cytotoxic T cell-mediated lysis ( 91 ). In addition, CRISPR/Cas9 screening also found that editing Asf1a ( 69 ), PRMT1 and RIPK1 ( 92 ), MAN2A1 ( 93 ), IFNGR2 and JAK1 ( 94 ) increased the sensitivity of tumors to anti-PD-1 or PD-L1 treatment. Tumor cells disrupt T-cell-mediated immune monitoring by maintaining high levels of PD-L1, while CRISPR/Cas9 screening found that the PD-L1 transcription and level, translation levels and maintenance of its stability and expression of oncogenic factors, thus exploring the related regulatory mechanisms of PD-L1 to provide a potential biologic therapeutic target for disrupting PD-L1-mediated tumor tolerance therapy.…”
Section: Crispr/cas9 Screening In Pd-1/pd-l1 Immunotherapymentioning
confidence: 99%